2012
DOI: 10.1038/modpathol.2012.30
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis of EPCAM expression loss in Lynch syndrome-associated tumors

Abstract: Germline deletions affecting the Epithelial cell adhesion molecule (EPCAM) gene lead to silencing of MSH2 and cause Lynch syndrome. We have recently reported that lack of EPCAM expression occurs in many, but not all tumors from Lynch syndrome patients with EPCAM germline deletions. The differences in EPCAM expression were not related to the localization of EPCAM germline deletions. We therefore hypothesized that the type of the second somatic hit, which leads to MSH2 inactivation during tumor development, dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 16 publications
(15 reference statements)
1
48
0
2
Order By: Relevance
“…However, somatic events involved in inactivation of the remaining allele of MSH2 have heretofore not been fully characterized. Huth et al (17) reported that four out of six various cancers that developed in LS patients with germline EPCAM deletions revealed homozygous EPCAM deletion in cancer tissue. On the other hand, a recent study by Spaepen et al (7) reported that one colorectal cancer developed in an LS patient with a large 4 Mb deletion including the EPCAM, MSH2 and MSH6 genes, while the other showed homozygous deletion of only the EPCAM gene.…”
Section: Discussionmentioning
confidence: 99%
“…However, somatic events involved in inactivation of the remaining allele of MSH2 have heretofore not been fully characterized. Huth et al (17) reported that four out of six various cancers that developed in LS patients with germline EPCAM deletions revealed homozygous EPCAM deletion in cancer tissue. On the other hand, a recent study by Spaepen et al (7) reported that one colorectal cancer developed in an LS patient with a large 4 Mb deletion including the EPCAM, MSH2 and MSH6 genes, while the other showed homozygous deletion of only the EPCAM gene.…”
Section: Discussionmentioning
confidence: 99%
“…9 As a result, an indicative FH would lead to further investigations in the event of no MMR mutation being found in a proband; such investigations are not included in the model. l Constitutional epimutations may not be detected by current methods, 273,274 and though at present they would be included in the model as negative diagnostic test results (with LS possibly being assumed on the basis of FH), it is possible that in the future further testing may be recommended for such mutations which could incur extra costs and affect cost-effectiveness. However, a doubling of the cost of diagnostic genetic testing did not have a significant impact on cost-effectiveness, except for strategy 8 (universal genetic testing).…”
Section: Strengths and Limitations Of The Peninsula Technology Assessmentioning
confidence: 99%
“…As far as we are aware, there have been no previous reports of this combination of gene mutations resulting in early onset colorectal cancer. The transcription of a mutated copy of EPCAM has been reported to result in downstream silencing of the adjacent MSH2 gene through transcriptional read-through 1. Immunohistochemistry in this case elegantly shows that complete absence of MSH2 expression can occur when one MSH2 allele is mutated, and the second allele is silenced with transcription of mutated copy of EPCAM .…”
mentioning
confidence: 71%
“…Rarely, LS can also arise due to germline deletion of the 3′ region of the epithelial cell adhesion molecule ( EPCAM ) gene, an event that results in silencing of the in cis downstream MSH2 gene in epithelial cells 1 2. As with other causes of LS, EPCAM mutations have been associated with increased risk of colorectal and endometrial carcinomas 3…”
mentioning
confidence: 99%